2020
DOI: 10.3855/jidc.12736
|View full text |Cite
|
Sign up to set email alerts
|

Rifampicin resistance patterns and dynamics of tuberculosis and drug-resistant tuberculosis in Enugu, South Eastern Nigeria

Abstract: Introduction: Tuberculosis (TB) continues to be a public health problem globally. The burden is further exacerbated in developing countries like Nigeria, by poor diagnosis, management and treatment, as well as rapid emergence of drug-resistant TB. This study was conducted to evaluate the prevalence of drug-resistant TB, determine the rpoB gene mutation patterns of Mycobacterium tuberculosis (MTB) and model the dynamics of multidrug resistant TB (MDR-TB) in Enugu, Nigeria. Methodology: A total of 868 samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
1
2
1
Order By: Relevance
“…The current study found that the most prevalent mutation in rpoB gene mutation in MTB was at probe E codon (529–533) (40.64%), followed by Probe D codon (523–529) 20.09% which was similar to studies done in Nigeria, Uganda, Pakistan, Addis Ababa Ethiopia, and Bangladesh (1317), the similarities suggests that a significant number of low-income individuals migrating for shelters may be responsible for the spread of mutant strains within the community (18). Our findings differed from the study done in Northeast India and Enugu, South Eastern Nigeria, which revealed that the most prevalent mutations were detected at probes A and D, respectively (19,20). The differences might be attributed to geographical differences caused by the variations in the M. tuberculosis lineage (21).…”
Section: Discussioncontrasting
confidence: 99%
“…The current study found that the most prevalent mutation in rpoB gene mutation in MTB was at probe E codon (529–533) (40.64%), followed by Probe D codon (523–529) 20.09% which was similar to studies done in Nigeria, Uganda, Pakistan, Addis Ababa Ethiopia, and Bangladesh (1317), the similarities suggests that a significant number of low-income individuals migrating for shelters may be responsible for the spread of mutant strains within the community (18). Our findings differed from the study done in Northeast India and Enugu, South Eastern Nigeria, which revealed that the most prevalent mutations were detected at probes A and D, respectively (19,20). The differences might be attributed to geographical differences caused by the variations in the M. tuberculosis lineage (21).…”
Section: Discussioncontrasting
confidence: 99%
“…The finding of this study shows that the mean age of the respondents is 35.71± 11.62 years, the overall prevalence of HIV among MDR-TB was 12.8% which is high compared to the national prevalence of 1.4% [8], this finding corroborates with the submission of Ugwu et al, [9]. They reported a prevalence rate of 16.7% in a similar study.…”
Section: Discussionsupporting
confidence: 89%
“…Measures to curtail the aggravating factors (such as poor diagnosis, management and treatment) to the TB infections should be put in emplace. Tuberculosis (TB) infections and the rapid emergence of drug-resistant TB remain public health concerns in developing countries and even the globe, Nigeria is not an exception to this (Ugwu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%